A new species of Acianthera (Pleurothallidinae, Orchidaceae) from Brazil - Rykaczewski, Max; Driessen, Wiel; Kolanowska, Marta (Phytotaxa, 2018)
A new species of Acianthera from Brazil is described and illustrated here. The novelty belongs to the nominal subgenus of Acianthera and it resembles Acianthera hystrix and A. portilloi but it is easily distinguishable by the external and internal pubescence of the sepals, the pubescent ovary and the lip disc ornamented with three lamellae. A dichotomous key to identification of all known species of Apoda-prorepentia group is provided.